Essays on mobile money services, microenterprises and role models in developing countries - Riley, E (2018)
Mobile money services have rapidly expanded across East Africa, with 66% of people using an account actively. Understanding the impact of these services is therefore an important area of research, which the first two chapters of my thesis contribute to. Chapter One of my thesis uses survey data from Tanzania to understand how mobile money services affect the risk sharing capabilities of households. I look at the aftermath of rainfall shocks at the village level, and examine how consumption has been affected for users of mobile money services, non-users who reside in villages with other users, and households that live in villages without access to mobile money services. I find that after a village-based rainfall shock, only users of mobile money services are able to smooth their consumption. Non-users, regardless of whether they have access to mobile money or not, experience a 6% fall in their consumption. This raises questions of who benefits from the introduction of new financial services. Chapter Two looks at integrating mobile money services into a microfinance loan product and the impact this has on the businesses of women in Uganda. In a field experiment, I randomly assigned women applying for a microfinance loan to receive the loan on a mobile money account or as cash. I find that women who receive their loan on a mobile money account invest 11% more of the loan into their business and experience 15% higher profits. These impacts are greatest for women who experienced high pressure to share money with family and friends at baseline. This study suggests that the manner in which a loan is disbursed has important implications for whether women are able to control how the loan is used. The third chapter of my thesis looks at a different topic: role models and how they impact behaviour. I study the impact of being randomly assigned to see a movie featuring a potential role model, Queen of Katwe, or a placebo movie, on the exam results of secondary school students in Uganda. Seeing Queen of Katwe results in lower secondary school students scoring 0.11 standard deviations higher in their maths exam, mainly because they are less likely to fail maths, and upper secondary school students scoring 0.13 standard deviations higher in their finishing exams. Impacts are largest for female students. Further research is needed to uncover the mechanisms by which a role model can raise exam performance, with both changing beliefs and raising aspirations potential channels.